2022
DOI: 10.3389/fnagi.2022.869708
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Temporal Fine Structure Sensitivity, Transient Storage Capacity, and Ultra-High Frequency Hearing Thresholds in Tinnitus Patients and Normal Adults of Different Ages

Abstract: BackgroundElderlies and tinnitus patients often find it challenging to process acoustic signals in noisy environments. The sensitivity to temporal fine structure (TFS), the transient storage capacity for TFS, and the ultra-high frequency (UHF) thresholds are all associated with aging-related damage, evidenced by speech-in-noise perception deficits. In the present study, we aimed to investigate the relationships among TFS sensitivity, transient storage capacity, and UHF thresholds in tinnitus patients and norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…For consistency and reproducibility, the parameters and procedures of the BIC delay threshold test have been described in detail in multiple previous studies ( Huang et al, 2009 ; Li et al, 2009 , 2013 ; Lei and Ding, 2021 ; Ding et al, 2022 ). There were two kinds of signals; in one presentation, the left-headphone noise was an exact copy of the right-headphone noise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For consistency and reproducibility, the parameters and procedures of the BIC delay threshold test have been described in detail in multiple previous studies ( Huang et al, 2009 ; Li et al, 2009 , 2013 ; Lei and Ding, 2021 ; Ding et al, 2022 ). There were two kinds of signals; in one presentation, the left-headphone noise was an exact copy of the right-headphone noise.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between interaural delay in binaural gap detection and sensitivity to TFS may vary in populations with different characteristics. A recent study (age range 21–65 years) found that the BIC delay threshold and TFS-AF tests were significantly correlated in a tinnitus group but not in a normal group, since binaural integration may be more difficult due to overt/covert hearing loss with aging and tinnitus ( Ding et al, 2022 ). However, both BIC delay threshold and TFS-AF tests are binaural-based tests that are likely to be affected by monaural coding of TFS information before binaural interaction ( Whiteford et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation